Concise Synthesis of Cinnamtannin A2 from Dimeric Epicatechin Electrophile and Nucleophile Prepared by Zn(OTf)2-Mediated Self-Condensation - Ichikawa, Mikihiro; Takanashi, Kohki; Suda, Manato; Hattori, Yasunao; Kawahara, Sei-ichi; Fujii, Hiroshi; Makabe, Hidefumi (Synthesis, 2016)
The synthesis of cinnamtannin A2 from dimeric epicatechin nucleophile and electrophile was accomplished. Dimeric epicatechin nucleophile was prepared directly by reduction of the C-4′′ 1-ethoxyethoxy group of the electrophile which was previously synthesized by us.
Keywords: phenols; Lewis acids; oligomerization; natural products; stereoselective synthesis